Outcomes after endovascular thrombectomy for acute ischemic stroke patients with active cancer: A systematic review and meta-analysis - Duan, Linyan; Fu, Zhaolin; Zhao, Hengxiao; Song, Chengyu; Tian, Qiuyue; Dmytriw, Adam A.; Regenhardt, Robert W.; Sun, Ziyi; Guo, Xiaofan; Wang, Xue; Yang, Bin (Frontiers in Neurology, 2022)
Background: Active cancer (AC) is a known risk factor for stroke and a common comorbidity among patients being considered for treatment with endovascular thrombectomy (EVT). This systematic review and meta-analysis aimed to evaluate the current evidence for the feasibility, efficacy, and safety of EVT for patients with AC. Methods: MEDLINE, EMBASE, and the Cochrane Library were searched for relevant randomized controlled trials (RCTs) and observational studies which met the inclusion criteria for EVT in AC patients. Studies were excluded due to the mismatch of data format, article type and group design. Risk of bias was assessed through different scales according to the study design. I2 statistics were used to evaluate the heterogeneity. Funnel plots was used to evaluate publication bias. Results: A total of 6 studies and 3,657 patients were included. Compared to without active cancer (WC) patients, AC patients had a significantly higher proportion of in-hospital mortality (OR 3.24; 95% CI, 1.03-10.15). The estimated rate of favorable outcome of 6 studies was lower in AC patients than in WC patients (OR 0.47; 95% CI, 0.35-0.65). For 90-day mortality of 4 studies, the AC group had a higher proportion when compared with the WC group (OR 3.87; 95% CI, 2.64-5.68). There was no difference between rate of 6 studies of successful recanalization (OR 1.24; 95% CI, 0.90-1.72) and 4 studies of symptomatic ICH (OR 1.09; 95% CI, 0.61-1.97) comparing AC and WC. Conclusions: Patients with AC are less likely to have a favorable outcome and have a higher risk of mortality after EVT. Further studies are warranted for this unique patient population.